Internet and language teaching - Puteh, Marlia; Hussin, Supyan (2003)
The Internet is increasingly used by Malaysian higher institutions. However, there is lack of evidence on the application of the Internet in the universities as well as the teachers’ view on their Internet application in language teaching. The aim of this research is to seek the perception of Malaysian English language lecturers on the use of Internet in language teaching and learning. Respondents who are teaching in two universities were the subjects of this research. Results show that most of the teachers applied the Internet in their language teaching and believed that the Internet is a valuable teaching tool.